2017
DOI: 10.1038/nature23879
|View full text |Cite
|
Sign up to set email alerts
|

Hardware-efficient variational quantum eigensolver for small molecules and quantum magnets

Abstract: Quantum computers can be used to address molecular structure, materials science and condensed matter physics problems, which currently stretch the limits of existing high-performance computing resources [1]. Finding exact numerical solutions to these interacting fermion problems has exponential cost, while Monte Carlo methods are plagued by the fermionic sign problem. These limitations of classical computational methods have made even few-atom molecular structures problems of practical interest for medium-size… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
2,921
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 2,663 publications
(3,046 citation statements)
references
References 27 publications
18
2,921
0
4
Order By: Relevance
“…It follows from (12) that the Fourier transform of the coefficients α i,± (t) consists of a series of peaks at integer multiples of the modulation frequency ω Φ with weights given by (13). Inserting the result (12) into (9) and (10) yields analogous expansions for the coupling parameters Ω ± (t) = k Ω ± (k)e ikωΦt and for the detunings ∆ ± (t) = k ∆ ± (k)e ikωΦt (which determine the phases ϕ ± (t)).…”
Section: Ii2 Xx±yy Couplingsmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows from (12) that the Fourier transform of the coefficients α i,± (t) consists of a series of peaks at integer multiples of the modulation frequency ω Φ with weights given by (13). Inserting the result (12) into (9) and (10) yields analogous expansions for the coupling parameters Ω ± (t) = k Ω ± (k)e ikωΦt and for the detunings ∆ ± (t) = k ∆ ± (k)e ikωΦt (which determine the phases ϕ ± (t)).…”
Section: Ii2 Xx±yy Couplingsmentioning
confidence: 99%
“…With superconducting circuits, single qubit quantum gates can be carried out with fidelities approaching 99.99% [1-4], while errors in two-qubit operations are typically higher with record fidelities around 99% [3,5]. However, the realization of qubit operations with even higher fidelity is required both for reaching the error threshold for quantum computation [6-9] and for carrying out reliable quantum simulations and optimizations in large arrays of coupled qubits [10][11][12][13]. Moreover, the quest for useful quantum computations before full quantum error correction becomes available may be assisted by efficient, short-depth gate sequences based on two-or multi-qubit gates [14,15] with versatile types of interactions.…”
mentioning
confidence: 99%
“…The mapping of Hamiltonian from H to H ′ can be written as: So far we are able to transform our Hamiltonian to a k-local Hamiltonian including only products of σ z terms. In the Supplementary Materials we show the details of the transformation to 2-local spin Hamiltonian but here we present an example of transforming 3-local to a 2-local Ising Hamiltonian [23].Here, we see that by including x 4 , one can show that minimizing 3-local is equivalent to minimizing the sum of 2-local terms.Finally, we succeed in transforming our initial complex electronic structure Hamiltonian from the secondquantization form to an Ising-type Hamiltonian which can be solved using existing quantum computing hardware [14,24,8,25].To illustrate this proposed method (details are in the Supplementary Materials), we present calculations for the Hydrogen molecule H 2 , the Helium dimer He 2 , HeH + diatomic molecule and the LiH molecule. First, we used the Bravyi-Kitaev transformation and the Jordan-Wigner transformation to convert the diatomic molecular Hamiltonian in the minimal basis set (STO-6G) to the spin Hamiltonian of (σ x , σ y , σ z ).…”
mentioning
confidence: 99%
“…This demonstrates that one can generally map the electronic ground state energy of a molecular Hamiltonian to an Ising-type Hamiltonian which could easily be implemented on presently available quantum hardware. Moreover, the recent experimental results for simple few electrons diatomic molecules presented by the IBM group have shown that a hardware-efficient optimizer implemented on a 6-qubit superconducting quantum processor is capable of producing the potential energy surfaces of such molecules [24]. The development of efficient quantum hardware and the possibility of mapping the electronic structure problem into an Ising-type Hamiltonian may grant efficient ways to obtain exact solutions to the Schrödinger equation, this being one of the most daunting computational problems present in both chemistry and physics.…”
mentioning
confidence: 99%
See 1 more Smart Citation